Experimental investigation on the strength and stiffness of 3D printed stainless steel S/S 316L parts - Ang, Pei Chang (Nanyang Technological University, 2024)
Additive manufacturing (AM) is a novel technique of producing complex near net-shape components, which may not be possible with conventional manufacturing techniques. However, due to the repetitive melting and rapid solidification involved in the manufacturing process, it may cause the specimen to exhibit anisotropic behaviour.